2016
DOI: 10.1212/cpj.0000000000000232
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of serum prolactin levels in PNES in the epilepsy monitoring unit

Abstract: This study provides Class III evidence that postevent elevation of serum prolactin occurs in 84.4% of patients with ES and 28.8% of patients with PNES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…However, patients with syncope may also experience mild prolactin elevation 14. Furthermore, a recent study of patients admitted to an epilepsy monitoring unit to distinguish psychogenic from epileptic seizures questioned the role of prolactin, with 29% and 16% false positive and false negative rates, respectively 15. Therefore, physicians ordering prolactin level for assessing seizures or pseudo-seizures should be cognisant of the above limitations.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with syncope may also experience mild prolactin elevation 14. Furthermore, a recent study of patients admitted to an epilepsy monitoring unit to distinguish psychogenic from epileptic seizures questioned the role of prolactin, with 29% and 16% false positive and false negative rates, respectively 15. Therefore, physicians ordering prolactin level for assessing seizures or pseudo-seizures should be cognisant of the above limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Usually normal [32,33] High sensitivity for FBTCS (up to 100%) [33] Relevant for bilateral convulsive episodes ES epileptic seizure, PNES psychogenic non-epileptic seizure, SE status epilepticus, FBTCS focal to bilateral tonic-clonic seizure, Sp specificity (%) for PNES or ES explanation that the application of a tuning fork on a precise point on the can induce a seizure. The physician can also stimulate multiple areas, explaining that there is a gradation of the ictogenic power of the tuning fork, depending on the stimulation point (Video 3 illustrates the tuning fork test with an example of answer depending on the stimulation site).…”
Section: Prolactin Levelmentioning
confidence: 99%
“…Concerning the relevant threshold, the increase is generally considered significant if there is a doubling from baseline (if this baseline is available, with a minimum of 15-16.5 ng/ml in post-ictal period) or if there is an increase over 45 ng/ml [32]. Sensitivity can go up to 100% for bilateral tonic-clonic seizures and more than 80% for focal seizures with impaired awareness [9,[31][32][33]. Abubakr and Wambacq have reported a false positive rate of 28% [33].…”
Section: Prolactin Levelmentioning
confidence: 99%
“…This was reinforced more recently by Ahmad et al (2019) in a 2-year cross-sectional study involving 90 participants, which found that prolactin levels were higher in those with tonic–clonic epileptic seizures than those with non-epileptic seizures. However, the evidence is not always consistent: in a 4-year retrospective study of 218 participants Abubakr & Wambacq (2016) reported that prolactin did not provide additional support when differentiating between epileptic and psychogenic non-epileptic seizures and concluded that it should not be routinely tested. A summary of when prolactin should be tested is contained in Box 2.…”
Section: Investigationsmentioning
confidence: 99%